2019
DOI: 10.46784/e-avm.v10i1.77
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Hydrometra in Goats and Therapeutic Effects

Abstract: The presence of hydrometra was analyzed on five dairy goat farms (one Saanen and four Alpine) in a period of one to three years, from 2013 to 2016. Total of 3,355 goats were scanned by ultrasound for pregnancy diagnosis after breeding season or out-of-season upon hormonal synchronization. Overall incidence of hydrometra was 1.37%. One farm of Saanen goats demonstrated statistically higher incidence of hydro/pyometra as compared to other four Alpine farms (3.25% vs. 0.56%; p <0.001). Seasonal synchronization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
(14 reference statements)
1
1
0
2
Order By: Relevance
“…The cure rate of 59% and pregnancy rate of 48% following two prostaglandin injections were reported before (Hesselink, 1993.b), which is lower than our nding. In another study, despite a 95% cure rate after the second prostaglandin administration, a pregnancy rate of 45% following treatment with three doses of prostaglandin was reported (Maia et al, 2018.b), another study reported conception rate of 64%, which is comparable to our result (Barna et al, 2017). Antibiotic administration improved the cure rate and pregnancy rate numerically, and the lack of signi cant results might be due small number of observations in each group of the study.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The cure rate of 59% and pregnancy rate of 48% following two prostaglandin injections were reported before (Hesselink, 1993.b), which is lower than our nding. In another study, despite a 95% cure rate after the second prostaglandin administration, a pregnancy rate of 45% following treatment with three doses of prostaglandin was reported (Maia et al, 2018.b), another study reported conception rate of 64%, which is comparable to our result (Barna et al, 2017). Antibiotic administration improved the cure rate and pregnancy rate numerically, and the lack of signi cant results might be due small number of observations in each group of the study.…”
Section: Discussionsupporting
confidence: 81%
“…There are some reports about a higher prevalence of PPG in cases of cyclicity out of the breeding season (Duquesnel et al, 1992;Barna et al, 2017). Moreover, a positive genetic correlation between out-ofseason kidding ability (and also extended lactation and whole-life days in milk, as a result) with PPG was reported.…”
Section: Discussionmentioning
confidence: 98%
“…Chez l'espèce caprine en milieu tropical, des fréquences comprises entre 1,3 et 10,5 % ont été rapportées au Soudan (Almubarak et al, 2018). Dans les zones tempérées, des fréquences de 3,8 % (Leboeuf et al, 1994) ont été rapportées en France, de 3 à 21 % selon les troupeaux en Hollande (Hesselink et Elving, 1996), et de 1,37 à 10,45 % en Serbie (Barna et al, 2017). Les chèvres adultes sont plus touchées que les (Zongo et al, 2014).…”
Section: Pseudo-gestationunclassified
“…Cette espèce développe cependant de nombreuses contraintes de reproduction dont la pseudogestation avec des moyennes comprises entre 1,3 et 10,5% (Barna et al, 2017 ;Almubarak et al, 2018). L'application de techniques de diagnostic précoce de gestation et de suivi du développement foetal revêt une valeur ajoutée considérable pour optimiser le taux de survie des nouveaux nés et améliorer le revenu des producteurs (Karen et al, 2014).…”
Section: Introductionunclassified